FENOMENOLOGI MAHASISWA DAERAH PROVINSI JAMBI DALAM MENGELOLA KONFLIK PENYESUAIAN KOMUNIKASI DI JAKARTA - Syubhan Akib; Ahmad Robert; Nanda Rahayu Haryadi; Agung Famungkas; Dedi Saputra (Berajah Journal, 2026)
This study examines the experiences of students from Jambi Province in managing communication adjustment conflicts while studying in Jakarta, using a phenomenological approach. The phenomenon of moving to a big city like Jakarta often presents various adaptation challenges, especially in terms of communication, caused by significant cultural differences. This study aims to understand the essence of these students' conscious experiences in facing the clash of values, norms, and communication habits between the collectivist Jambi Malay culture and the individualistic urban culture of Jakarta. Using in-depth interviews with purposively selected participants, this study identified four main themes that describe their transformative journey. These themes include language failure due to differences in dialect and speech speed, difficulties navigating norms, Jakarta's directness in contrast to Jambi's culture of small talk, the development of coping strategies such as mimicry and strengthening ethnic communities, and finally the formation of a hybrid communicative identity. The results show that this communication conflict directly impacts psychological aspects such as anxiety and decreased self-esteem, but through various strategies, the students successfully transformed this conflict into a new skill and identity strength.